Boron carbide nano-powder and preparation method of boron carbide nano-powder ceramic

By combining amorphous carbon coating and solid phase reaction method for nanoscale hexagonal boron nitride, the problems of boron carbide densification and powder agglomeration are solved, and high-quality boron carbide nanopowder preparation and sintering performance are improved.

CN119569061AActive Publication Date: 2025-03-07JINGGANGSHAN UNIVERSITY +1

Patent Information

Application Number
CN202411805618.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-03-07
Estimated Expiration
2044-12-10

AI Technical Summary

Technical Problem

The prior art is difficult to achieve densification of single-phase boron carbide without adding a sintering aid, and there is a problem that powder aggregation and insufficient reaction of the carbon coating layer with boron nitride.

Method used

The nano-sized hexagonal boron nitride is coated with amorphous carbon surface, and the reaction between the carbon source and boron nitride is promoted through the solid phase reaction method. The two carbon coating method is used to control the carbon coating situation and reaction effect.

Benefits of technology

While preventing the agglomeration of boron nitride powder, it promotes the reaction between the carbon source and boron nitride, improves the quality of boron carbide nanopowder, and can use hexagonal boron nitride with smaller particle size to obtain boron carbide nanopowder with smaller particle size and improves its sintering performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119569061A_ABST
    Figure CN119569061A_ABST
Patent Text Reader

Abstract

The preparation method comprises the following steps that hexagonal boron nitride is subjected to carbon coating treatment through a carbon source, then the carbon source is placed in a vacuum reaction furnace at the temperature of 1500-2000 DEG C to be subjected to a solid-phase reaction, and the carbon source comprises a carbohydrate compound and an oxygen-containing compound; the carbon coating treatment comprises the following steps: (1) mixing a carbohydrate compound and hexagonal boron nitride, carrying out ball milling, adding water into the obtained mixed powder, uniformly dispersing, and then carrying out hydrothermal carbonization to obtain primary carbon-coated boron nitride; and (2) spraying an oxygen-containing compound on the surface of the primary carbon-coated boron nitride obtained in the step (1), cooling, drying, carrying out closed carbonization at 500-1000 DEG C for 3-6 hours, and naturally cooling to obtain secondary carbon-coated boron nitride. According to the method, the carbon source is directly adopted to perform surface amorphous carbon coating on the nanoscale hexagonal boron nitride, so that the boron nitride powder is prevented from being agglomerated, the reaction of the carbon source and the boron nitride can be promoted, and the quality of the boron carbide nano powder is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of ceramic materials, and in particular relates to a method for preparing boron carbide nanopowder and ceramics thereof. Background Art

[0002] Boron carbide (B4C) ceramics have a low density (2.52 g / cm 3 ), high melting point (2450℃), high hardness (second only to diamond and cubic boron nitride) and good thermal neutron absorption ability, etc., it has a wide range of application prospects in protection, wear resistance and nuclear energy. However, due to the strong covalent bond of boron carbide, it is very difficult to densify it.

[0003] At present, some studies have promoted its densification by introducing sintering aids, but the addition of sintering aids may have an adverse effect on material properties, such as an increase in theoretical density and a decrease in hardness, which limits the application of boron carbide ceramics to a certain extent. In order to achieve the densification of single-phase boron carbide without adding sintering aids, the inventor's research and development team has reported the use of a solid phase reaction method to synthesize boron carbide nanopowders by solid phase reaction of hexagonal boron nitride and carbon black or graphite under high temperature vacuum (Zeng Hong, Kan Yanmei, Xu Changming, etc., Synthesis of boron carbide nanopowders by solid phase reaction, Journal of Inorganic Materials, Vol. 26, No. 10, October 2011). This method can obtain boron carbide nanopowders with an average particle size of 100nm and has good sintering activity. However, in order to obtain fine and uniform boron nitride nanopowders in this method, the hexagonal boron nitride, carbon black, etc. used are all nano-level powders, which have partial agglomeration, which affects both the activity of the solid-phase reaction and the particle size distribution of the final product boron nitride. In addition, there are great restrictions on the particle size of the reaction raw materials hexagonal boron nitride, carbon black, etc., and raw materials with smaller particle sizes cannot be used.

[0004] In the prior art, the agglomeration of nanopowders is generally solved by adding dispersants or performing surface grafting modification on the powders. However, when this method is applied to the solid-phase reaction method for synthesizing boron carbide nanopowders, it is easy to form an organic group barrier layer on the surface of boron nitride, carbon black, etc., which affects the reaction activity between powders. Even if these organic groups can be decomposed in the subsequent high-temperature reaction process, the small molecular impurities produced by the decomposition are easy to affect the purity of the boron carbide nanopowder (such as oxygen content), thereby affecting the sintering performance.

[0005] CN102502535A provides a method for preparing carbon-coated hexagonal boron nitride, which uses maleic anhydride ethylene octene graft copolymer as a carbon source to carbon-coat hexagonal boron nitride, and its purpose is to obtain carbon-coated hexagonal boron nitride with good dispersibility and good wear resistance. CN112662449A provides a highly dispersed amorphous carbon-coated hexagonal boron nitride nanosheet and a preparation method thereof, which uses sugar as a carbon source to carbon-coat hexagonal boron nitride nanosheets, giving it dispersibility and lubrication and friction-reducing effects. Although the above two patents can improve the dispersibility of boron nitride, they do not take into account the reaction problem between the carbon coating layer and the hexagonal boron nitride, and simply perform surface carbon coating on the hexagonal boron nitride.

[0006] CN108249443A provides a method for preparing carbon-encapsulated boron carbide nanopowder, which uses boric acid as a boron source and sucrose as a carbon source to prepare carbon-encapsulated boron carbide nanopowder under high vacuum reaction conditions. However, this method is a coating of the boron carbide nanopowder, and this method allows excessive carbon to be used as a sintering aid, which is likely to affect the sintering performance of boron carbide.

[0007] The existing document "Study on the synthesis of boron carbide powder by low-temperature precursor pyrolysis, Lin Shuang" uses polyvinyl alcohol, glucose, soluble starch and sucrose and other hydroxyl-containing organic carbon as carbon sources, boric acid as boron source, and adopts esterification method to synthesize polymer precursors, and prepares B4C powder by pyrolysis and vacuum sintering. This method is to synthesize boron carbide powder after esterification between carbon source and boron source. This method is suitable for specific types of carbon source and boron source that can undergo esterification reaction. And this document and patent CN108249443A do not consider the carbon coating problem of hexagonal boron nitride in the preparation process of boron carbide nanopowder.

[0008] In summary, how to provide a method for preparing boron carbide nanopowder and ceramics thereof, which can prevent the agglomeration of the reaction raw material powders and promote the reaction of the carbon source and the boron source, is an urgent problem to be solved. Summary of the invention

[0009] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a method for preparing a boron carbide nanopowder and a ceramic thereof, wherein a carbon source is directly used to coat the surface of nano-scale hexagonal boron nitride with amorphous carbon, thereby preventing the agglomeration of boron nitride powder and promoting the reaction between the carbon source and boron nitride, thereby improving the quality of the boron carbide nanopowder.

[0010] In order to achieve the above object, the technical solution adopted by the present invention is: A method for preparing boron carbide nanopowder comprises the following steps: using a carbon source to perform carbon coating treatment on hexagonal boron nitride, and then placing the hexagonal boron nitride in a vacuum reactor for solid phase reaction, wherein the carbon source comprises a saccharide compound and an oxygen-containing compound.

[0011] Preferably, the molar ratio of the carbon source, calculated as C, to hexagonal boron nitride is (1.1-1.6):4, and the diameter of the hexagonal boron nitride is 0.001-50 μm, more preferably 10-500 nm, and even more preferably 50-100 nm.

[0012] Preferably, the mass ratio of the carbohydrate compound to the oxygen-containing compound is (0.5-2):1, the carbohydrate compound comprises hexose and pentose in a mass ratio of 1:(0.3-0.6), the hexose is one or more of glucose, mannose, fructose and galactose, and the pentose is one or two of xylose and deoxyribose; the number of oxygen atoms in the oxygen-containing compound accounts for 10-24%, and the oxygen-containing compound is one or more of polyethylene glycol (polymerization degree of 5-50, oxygen atoms account for 14.4-15.8%), poly (ethylene glycol) tetrahydrofurfuryl ether (polymerization degree of 1-50, oxygen atoms account for 12.5-14.2%), mannitol, and sorbitol.

[0013] Preferably, the temperature of the solid phase reaction in the vacuum reaction furnace is 1500-2000°C, the heating rate is 30-50°C, the insulation time is 3-6h, and the vacuum degree in the vacuum reaction furnace is (0.1-10)×10 -4 Pa.

[0014] The carbon coating process comprises the following steps: (1) The sugar compound and hexagonal boron nitride are mixed and ball-milled, the obtained mixed powder is evenly dispersed by adding water, and then hydrothermal carbonization is performed to obtain the first carbon-coated boron nitride; (2) Spraying an oxygen-containing compound (which can be dissolved into a solution by adding a solvent, the mass concentration of the solution is 40-80%, and the solvent is water, ethanol, glycerol or propylene glycol) onto the surface of the first carbon-coated boron nitride obtained in step (1), cooling and drying, placing it in a closed state for carbonization at 500-1000°C for 3-6 hours, and cooling it naturally to obtain a second carbon-coated boron nitride.

[0015] Preferably, in step (1), the ball milling rate is 300-500 rpm, and the ball milling time is 3-8 h; the hydrothermal carbonization conditions are: 160-250° C., a heating rate of 1-10° C. / min, and insulation for 2-4 h.

[0016] In step (2), the carbonization heating rate is 5-30°C / min.

[0017] Preferably, in order to further promote the solid phase reaction effect, sodium chloride is also added during the second carbon coating in the present invention. At this time, the oxygen-containing compound is preferably sorbitol, polyethylene glycol (degree of polymerization is 5-50) and poly (ethylene glycol) tetrahydrofurfuryl ether (degree of polymerization is 1-50), and the mass ratio of the three is (0.001-0.004): (0.2-0.8): 1.

[0018] Preferably, in the case of adding sodium chloride, the carbon coating process comprises the following steps: (1) The sugar compound and hexagonal boron nitride are mixed and ball-milled, the obtained mixed powder is evenly dispersed by adding water, and then hydrothermal carbonization is performed to obtain the first carbon-coated boron nitride; (2) Spraying a solution formed by a mixture of a saturated sodium chloride aqueous solution and sorbitol onto the surface of the first carbon-coated boron nitride obtained in step (1), and then placing it at 70-80°C for constant temperature evaporation for 1-3 hours, and then continuing to spray polyethylene glycol and poly (ethylene glycol) tetrahydrofurfuryl ether, drying after spraying, first placing it at 500-750°C for vacuum carbonization for 2-5 hours, and then heating it to 850-1000°C and keeping it warm for 0.5-1 hour, and then cooling it naturally, repeatedly washing it with clean water to remove sodium chloride, and drying it to obtain a second carbon-coated boron nitride.

[0019] Preferably, the amount of sodium chloride added is 1-6% of the mass of the oxygen-containing compound, the rate of heating to 500-750°C is 5-20°C / min, and the rate of heating to 850-1000°C is 15-30°C / min.

[0020] Preferably, the change process of the vacuum degree in the vacuum reaction furnace during the solid phase reaction is as follows: Before heating to 1500-2000℃, the vacuum degree is (6-10)×10 -4 Pa; During the 0-1h period of heating to 1500-2000℃, the vacuum degree is (3-5)×10 -4 Pa; During the first 2 hours of heating to 1500-2000℃, the vacuum degree is (0.1-1)×10 -4 Pa; During the 2-6h period of heating to 1500-2000℃, the vacuum degree is (2-4)×10 -4 Pa.

[0021] The present invention also provides a method for sintering boron carbide nanopowder, comprising the following steps: sintering the boron carbide nanopowder prepared above at 1900-2100° C. and 28-32 MPa in an inert gas atmosphere (argon or helium) for 40-70 minutes to obtain the boron carbide nanopowder.

[0022] The present invention also provides a boron carbide ceramic, which is made by the above sintering method.

[0023] Technical effects of the present invention: 1. The present invention directly uses a carbon source to coat the surface of nano-scale hexagonal boron nitride with amorphous carbon, which can prevent the agglomeration of boron nitride powder and promote the solid phase reaction of the carbon source and boron nitride. The existing technology does not take into account the reaction between the carbon coating layer and boron nitride when carbon coating boron nitride. In order to take into account both carbon coating and reactivity (the ordinary coating amount is too small to react completely, and the coating amount is too large and the excess carbon affects the purity and sintering performance of the boron carbide product), the present invention uses a double coating method for coating, which can better control the carbon coating situation and reaction effect, and can use hexagonal boron nitride with a smaller particle size (the smaller the particle size, the higher the reaction activity), to obtain a boron carbide nanopowder with a smaller particle size.

[0024] 2. When the surface of hexagonal boron nitride is carbon-coated, the present invention first uses a sugar compound for the first hydrothermal carbon coating. The carbon-coated surface contains more oxygen-containing groups, which can have good compatibility with the oxygen-containing compounds of the second carbon coating, thereby promoting the effect of the second carbon coating. In addition, the present invention uses a certain proportion of hexose and pentose as carbonization materials in the first carbon coating. The hydrothermal intermediate of hexose is hydroxymethylfurfural, which is hydrophilic and has good compatibility in water, but the carbonization product is easy to adhere. The hydrothermal intermediate of pentose is furanaldehyde, which is relatively hydrophobic. The carbonization product has good dispersibility and is not easy to adhere, but has poor compatibility with the oxygen-containing compounds of the second carbon coating, which affects the effect of the second carbon coating. Therefore, the hexose and pentose are mixed in a certain proportion for hydrothermal carbonization, which can improve the hydrothermal carbonization effect while taking into account the effect of the second carbon coating.

[0025] 3. In the second carbon coating of hexagonal boron nitride, the carbonization material used in the present invention is an oxygen-containing compound. During the high-temperature carbonization process of the second carbon coating, the oxygen atoms can be removed by high temperature and generate channels in the carbon coating layer, which can increase the specific surface area of ​​the product and promote the solid phase reaction of amorphous carbon and boron nitride. The proportion of oxygen atoms in the oxygen-containing compound has a great influence on the solid phase reaction. When the proportion of oxygen atoms is too low, there are fewer channels in the carbon coating layer, the solid phase reaction efficiency is insufficient, and it is easy to cause an excessively high graphitized structure, affecting the solid phase reaction; when the proportion of oxygen atoms is too high, there are too many channels in the carbon coating layer, resulting in an insufficiently strong structure, and the increase of oxygen atoms is easy to promote the formation of carbon oxides, resulting in carbon loss, resulting in insufficient carbon source and insufficient reaction. Therefore, the present invention selects the proportion of oxygen atoms in the oxygen-containing compound to be 10-24%, which can comprehensively improve the solid phase reaction effect.

[0026] 4. Compared with the prior art in which only the hydrothermal method is used to obtain the coating layer during carbon coating, which has a higher oxygen content and causes many defects, the present invention can not only remove the oxygen atoms in the second carbon coating layer through the second carbon coating high-temperature carbonization, but also remove the oxygen atoms in the coating layer formed by the first carbon coating hydrothermal carbonization, thereby reducing defects.

[0027] 5. In the present invention, a saturated sodium chloride solution is added to the oxygen-containing compound (sorbitol, which is a common additive for forming star-shaped dendrites) during the second carbon coating. The sodium chloride is first heated and evaporated in the presence of sorbitol to form star-shaped dendrites, which are highly dispersed crystals. The oxygen-containing compound (polyethylene glycol and poly(ethylene glycol) tetrahydrofurfuryl ether) added subsequently forms amorphous carbon based on the star-shaped dendrites during the first high-temperature carbonization process at 500-750°C, further improving the reactivity of the second carbon coating layer. Then, in the second high-temperature carbonization process at 850-1000°C, the sodium chloride crystals melt to form a highly fluid liquid that can flow in the gaps of the carbon coating, reducing the retention and reaction of small molecule compounds and promoting the removal of small molecule compounds, thereby comprehensively reducing the oxygen content of the carbon coating and improving the sintering performance of boron carbide; finally, the highly water-soluble sodium chloride is removed by washing with clean water, leaving pores of the specific crystal structure in the carbon coating, thereby improving the reaction activity of the carbon coating and sodium chloride will not remain in the nano boron carbide powder.

[0028] The oxygen-containing compound of the present invention includes a relatively large content of poly(ethylene glycol) tetrahydrofurfuryl ethyl ether, which is a liquid with gel properties at room temperature and can be well covered on the surface of sodium chloride crystals and highly dispersed before high-temperature carbonization, thereby improving the carbonization efficiency of poly(ethylene glycol) tetrahydrofurfuryl ethyl ether and the carbonization rate.

[0029] 6. Small-particle boron carbide powder can improve sintering density. The particle size of the boron carbide nanopowder obtained by the present invention is small, but its sintering performance (density, toughness) is not significantly improved compared with the prior art. This may be because after the present invention performs secondary carbon coating on hexagonal boron nitride, the discharge of nitrogen generated by boron nitride in the coating layer during the solid phase reaction is delayed, making the structure of the boron carbide nanopowder loose and rough, and the friction between the powders is enhanced. In addition, since the particle size of the boron carbide nanopowder obtained in this application is small and the adhesion between the powders is large, the fluidity of the boron carbide powder is poor during application, which increases the difficulty of densification during the sintering process of the boron carbide powder, thereby affecting the sintering performance.

[0030] Therefore, in the process of preparing boron carbide nanopowder, the present invention adopts different vacuum degrees in different reaction stages, applies a lower vacuum degree in the early stage before a violent reaction, and applies a higher vacuum degree in the subsequent violent reduction reaction process, so that the nitrogen generated by the reaction can be discharged through the pores of the carbon coating layer in time, and no loose pores are caused in the synthesized boron carbide powder. Then, in the process of the subsequent reaction gradually slowing down, the vacuum degree is reduced to adapt to the solid phase reaction speed. Boron carbide with better sintering performance can be obtained through such a specific vacuum degree curve. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 This is an electron microscope scanning image of the boron carbide nanopowder prepared in an embodiment of the present invention; Figure 2 The XRD spectrum of the boron carbide nanopowder prepared in the present invention. DETAILED DESCRIPTION

[0032] The above scheme is further described below in conjunction with specific embodiments; it should be understood that these embodiments are used to illustrate the basic principles, main features and advantages of the present invention, and the present invention is not limited to the scope of the following embodiments; the implementation conditions adopted in the embodiments can be further adjusted according to specific requirements, and the implementation conditions not specified are usually the conditions in conventional experiments.

[0033] Unless otherwise specified in the following examples, all raw materials are commercially available or prepared by conventional methods in the art. Example 1

[0034] The present embodiment provides a method for preparing boron carbide nanopowder, comprising the following steps: after hexagonal boron nitride (100 nm) is subjected to carbon coating treatment using a carbon source, the solid phase reaction is carried out in a vacuum reactor, wherein the solid phase reaction temperature in the vacuum reactor is 1800°C, the heating rate is 40°C, the holding time is 3 hours, and the vacuum degree in the vacuum reactor is 1×10 -4 Pa.

[0035] The carbon source is calculated as C, and the molar ratio of the carbon source to hexagonal boron nitride is 1.3:4. The carbon source includes a sugar compound and an oxygen-containing compound in a mass ratio of 1.2:1, the sugar compound includes a hexose (glucose) and a pentose (xylose) in a mass ratio of 1:0.45, and the oxygen-containing compound is polyethylene glycol 1000.

[0036] The carbon coating process includes the following steps: (1) The sugar compound and hexagonal boron nitride were mixed and ball-milled at a ball-milling rate of 400 rpm for 5 h. The obtained mixed powder was evenly dispersed by adding water, and then hydrothermal carbonization was performed. The hydrothermal carbonization conditions were: 200 °C, a heating rate of 5 °C / min, and heat preservation for 3 h to obtain the first carbon-coated boron nitride; (2) Spraying an oxygen-containing compound (polyethylene glycol 1000 dissolved in water to form a solution with a mass concentration of 50%) onto the surface of the first carbon-coated boron nitride obtained in step (1), cooling and drying, and then placing it in a closed state for carbonization at 650°C for 4 hours, with a carbonization heating rate of 20°C / min. After the carbonization is completed, naturally cooling is performed to obtain a second carbon-coated boron nitride.

[0037] The present invention also provides a method for sintering boron carbide nanopowder, comprising the following steps: sintering the boron carbide nanopowder prepared above at 2000° C. and 30 MPa in an inert gas atmosphere (argon) for 55 minutes to obtain boron carbide nanopowder.

[0038] The present invention also provides a boron carbide ceramic, which is made by the above sintering method. Example 2

[0039] The difference between this embodiment and embodiment 1 is that the hexose in the carbohydrate compound is fructose and the pentose is deoxyribose. Example 3

[0040] The difference between this embodiment and embodiment 1 is that the oxygen-containing compound is poly(ethylene glycol) tetrahydrofurfuryl ethyl ether (polymerization degree of 1-2 components is 95-100%). Example 4

[0041] The difference between this embodiment and embodiment 1 is that the oxygen-containing compound is sorbitol (the number of oxygen atoms accounts for 23.1%). Example 5

[0042] The difference between this embodiment and embodiment 1 is that the oxygen-containing compound comprises polyethylene glycol 1000 and poly(ethylene glycol) tetrahydrofurfuryl ethyl ether in a mass ratio of 0.5:1 (the component with a degree of polymerization of 1-2 is 95-100%). Example 6

[0043] The difference between this embodiment and embodiment 1 is that the oxygen-containing compound includes sorbitol, polyethylene glycol 1000 and poly(ethylene glycol) tetrahydrofurfuryl ether in a mass ratio of 0.003:0.5:1 (the component with a degree of polymerization of 1-2 is 95-100%). Example 7

[0044] This embodiment provides a method for preparing boron carbide nanopowder, which is different from Example 1 in that the oxygen-containing compound includes sorbitol, polyethylene glycol 1000 and poly(ethylene glycol) tetrahydrofurfuryl ether (polymerization degree of 1-2 components is 95-100%) in a mass ratio of 0.003:0.5:1. Sodium chloride is also added during the carbon coating treatment, and the amount of sodium chloride added is 3% of the mass of the oxygen-containing compound. The carbon coating treatment specifically includes the following steps: (1) The sugar compound and hexagonal boron nitride were mixed and ball-milled at a ball-milling rate of 400 rpm for 5 h. The obtained mixed powder was evenly dispersed by adding water, and then hydrothermal carbonization was performed. The hydrothermal carbonization conditions were: 200 °C, a heating rate of 5 °C / min, and heat preservation for 3 h to obtain the first carbon-coated boron nitride; (2) Spray a solution formed by a mixture of saturated sodium chloride aqueous solution and sorbitol onto the surface of the first carbon-coated boron nitride obtained in step (1), then place it at 75°C for constant temperature evaporation for 2 hours, and then continue to spray polyethylene glycol 1000 and poly (ethylene glycol) tetrahydrofurfuryl ether. After spraying, dry it, first place it at 600°C (heating rate of 10°C / min) for vacuum carbonization for 3.5 hours, then heat it to 900°C (heating rate of 20°C / min) and keep it warm for 40 minutes, then cool it naturally, rinse it repeatedly with clean water to remove sodium chloride, and dry it to obtain the second carbon-coated boron nitride.

[0045] The rest is the same as Example 1. Example 8

[0046] This embodiment provides a method for preparing boron carbide nanopowder, which is different from Embodiment 7 in that the change process of the vacuum degree in the vacuum reaction furnace during the solid phase reaction is as follows: Before heating to 1800℃, the vacuum degree was 8×10 -4 Pa; The temperature was raised to 1800℃ and kept for 0-1h, and the vacuum degree was 4×10 -4 Pa; During the first 2 hours of heating to 1800℃, the vacuum degree was 0.5×10 -4 Pa; The temperature was raised to 1800℃ and kept for 2-3 hours, and the vacuum degree was 3×10 -4 Pa.

[0047] The rest is the same as Example 7. Example 9

[0048] The present embodiment provides a method for preparing boron carbide nanopowder, comprising the following steps: hexagonal boron nitride (50 nm) is carbon-coated with a carbon source, and then placed in a vacuum reactor for solid-phase reaction, wherein the temperature of the solid-phase reaction in the vacuum reactor is 1500° C., the heating rate is 30° C., and the insulation time is 4 hours.

[0049] The carbon source is calculated as C, and its molar ratio to hexagonal boron nitride is 1.1:4. The carbon source includes a sugar compound and an oxygen-containing compound in a mass ratio of 0.5:1, the sugar compound includes a hexose (glucose) and a pentose (xylose) in a mass ratio of 1:0.3, and the oxygen-containing compound includes sorbitol, polyethylene glycol 1000 and poly (ethylene glycol) tetrahydrofurfuryl ether in a mass ratio of 0.001:0.2:1 (the component with a degree of polymerization of 1-2 is 95-100%).

[0050] The carbon coating process includes the following steps: (1) The sugar compound and hexagonal boron nitride were mixed and ball-milled at a ball-milling rate of 300 rpm for 8 h. The obtained mixed powder was evenly dispersed by adding water, and then hydrothermal carbonization was performed. The hydrothermal carbonization conditions were: 160 ° C, a heating rate of 1 ° C / min, and a heat preservation time of 4 h to obtain the first carbon-coated boron nitride; (2) Spray a solution formed by a mixture of saturated sodium chloride aqueous solution and sorbitol onto the surface of the first carbon-coated boron nitride obtained in step (1), then place it at 70°C for constant temperature evaporation for 3 hours, then continue to spray polyethylene glycol 1000 and poly (ethylene glycol) tetrahydrofurfuryl ether, dry it after spraying, first place it at 500°C (heating rate of 5°C / min) for vacuum carbonization for 5 hours, then heat it to 850°C (heating rate of 15°C / min) and keep it for 1 hour, then cool it naturally, rinse it repeatedly with clean water to remove sodium chloride, and dry it to obtain the second carbon-coated boron nitride. The amount of sodium chloride added is 1% of the mass of the oxygen-containing compound.

[0051] The change process of vacuum degree in the vacuum reactor during solid phase reaction is as follows: Before heating to 1500℃, the vacuum degree was 6×10 -4 Pa; The temperature was raised to 1500℃ and the vacuum degree was 3×10 -4 Pa; During the first 2 hours of heating to 1500℃, the vacuum degree was 0.1×10 -4 Pa; The temperature was raised to 1500℃ and kept for 2-4 hours, and the vacuum degree was 2×10 -4 Pa.

[0052] The present invention also provides a method for sintering boron carbide nanopowder, comprising the following steps: sintering the boron carbide nanopowder prepared above at 1900° C. and 28 MPa inert gas atmosphere (argon) for 70 minutes to obtain boron carbide nanopowder.

[0053] The present invention also provides a boron carbide ceramic, which is made by the above sintering method. Example 10

[0054] The present embodiment provides a method for preparing boron carbide nanopowder, comprising the following steps: hexagonal boron nitride (200 nm) is subjected to carbon coating treatment using a carbon source, and then placed in a vacuum reactor for solid phase reaction, wherein the temperature of the solid phase reaction in the vacuum reactor is 2000° C., the heating rate is 50° C., and the insulation time is 6 hours.

[0055] The carbon source is calculated as C, and its molar ratio to hexagonal boron nitride is 1.6:4. The carbon source includes a sugar compound and an oxygen-containing compound in a mass ratio of 2:1, the sugar compound includes a hexose (glucose) and a pentose (xylose) in a mass ratio of 1:0.6, and the oxygen-containing compound includes sorbitol, polyethylene glycol 1000 and poly (ethylene glycol) tetrahydrofurfuryl ether in a mass ratio of 0.004:0.8:1 (the component with a degree of polymerization of 1-2 is 95-100%).

[0056] The carbon coating process includes the following steps: (1) The sugar compound and hexagonal boron nitride were mixed and ball-milled at a ball-milling rate of 500 rpm for 3 h. The obtained mixed powder was evenly dispersed by adding water, and then hydrothermal carbonization was performed. The hydrothermal carbonization conditions were: 250 ° C, a heating rate of 10 ° C / min, and heat preservation for 2 h to obtain the first carbon-coated boron nitride; (2) Spray a solution formed by a mixture of saturated sodium chloride aqueous solution and sorbitol onto the surface of the first carbon-coated boron nitride obtained in step (1), then place it at 80°C for constant temperature evaporation for 1 hour, then continue to spray polyethylene glycol and poly (ethylene glycol) tetrahydrofurfuryl ether, dry it after spraying, first place it at 750°C (heating rate of 20°C / min) for vacuum carbonization for 2 hours, then heat it to 1000°C (heating rate of 30°C / min) and keep it for 0.5 hours, then cool it naturally, rinse it repeatedly with clean water to remove sodium chloride, and dry it to obtain the second carbon-coated boron nitride. The amount of sodium chloride added is 6% of the mass of the oxygen-containing compound.

[0057] The change process of vacuum degree in the vacuum reactor during solid phase reaction is as follows: Before heating to 2000℃, the vacuum degree is 10×10 -4 Pa; The temperature was raised to 2000℃ and kept for 0-1h, and the vacuum degree was 5×10 -4 Pa; During the first 2 hours of heating to 2000℃, the vacuum degree was 1×10 -4 Pa; During the 2-6h period of heating to 2000℃, the vacuum degree was 4×10 -4 Pa.

[0058] The present invention also provides a method for sintering boron carbide nanopowder, comprising the following steps: sintering the boron carbide nanopowder prepared above at 2100° C. and 32 MPa inert gas atmosphere (argon) for 40 minutes to obtain boron carbide nanopowder.

[0059] The present invention also provides a boron carbide ceramic, which is made by the above sintering method.

[0060] Comparative Example 1 The difference between this comparative example and Example 6 is that the molar ratio of the carbon source, calculated as C, to the hexagonal boron nitride is 0.9:4.

[0061] Comparative Example 2 The difference between this comparative example and Example 6 is that the molar ratio of the carbon source, calculated as C, to hexagonal boron nitride is 2.0:4.

[0062] Comparative Example 3 The difference between this comparative example and Example 6 is that the carbon source does not contain a carbohydrate compound. In this case, an oxygen-containing compound is used to replace the hexagonal boron nitride during the first carbon coating. Step (1) is: the oxygen-containing compound (sorbitol, polyethylene glycol 1000, poly (ethylene glycol) tetrahydrofurfuryl ether, dissolved in water to form a solution with a mass concentration of 50%) and hexagonal boron nitride are mixed and ball milled at a ball milling rate of 400 rpm for 5 h. The obtained mixed powder is evenly dispersed by adding water, and then hydrothermal carbonization is performed. The hydrothermal carbonization conditions are: 200°C, a heating rate of 5°C / min, and a heat preservation time of 3 h to obtain the first carbon-coated boron nitride.

[0063] Comparative Example 4 The difference between this comparative example and Example 6 is that the carbon source does not contain oxygen-containing compounds. In this case, a sugar compound is used instead of the hexagonal boron nitride for the second carbon coating. Step (2) is: spraying a sugar compound (glucose and xylose dissolved in water to form a solution with a mass concentration of 50%) on the surface of the first carbon-coated boron nitride obtained in step (1), cooling and drying, and then placing it in a closed carbonization at 650°C for 4 hours. The carbonization heating rate is 20°C / min. After the carbonization is completed, it is naturally cooled to obtain the second carbon-coated boron nitride.

[0064] Comparative Example 5 The difference between this comparative example and Example 6 is that the carbon source does not contain oxygen-containing compounds, and the carbon coating process only includes step (1), that is, only the first carbon coating is performed.

[0065] Comparative Example 6 The difference between this comparative example and Example 6 is that the carbon source does not contain a sugar compound, and the carbon coating treatment in this case only includes step (2), directly carbon coating the oxygen-containing compound on the surface of hexagonal boron nitride.

[0066] Comparative Example 7 The difference between this comparative example and Example 6 is that the carbonization temperature in step (1) is the same as that in step (2), which is 650°C.

[0067] Comparative Example 8 The difference between this comparative example and Example 6 is that the carbonization temperature in step (2) is the same as that in step (1), which is 200°C.

[0068] Comparative Example 9 The difference between this comparative example and Example 6 is that the carbon source does not contain glucose.

[0069] Comparative Example 10 The difference between this comparative example and Example 6 is that the carbon source does not contain xylose.

[0070] Comparative Example 11 The difference between this comparative example and Example 6 is that in the carbohydrate compound, the mass ratio of hexose to pentose is 1:0.1.

[0071] Comparative Example 12 The difference between this comparative example and Example 6 is that in the carbohydrate compound, the mass ratio of hexose to pentose is 1:0.8.

[0072] Comparative Example 13 The difference between this comparative example and Example 6 is that the oxygen-containing compound in the carbon source is glucose (the number of oxygen atoms accounts for 25%).

[0073] Comparative Example 14 The difference between this comparative example and Example 6 is that the oxygen-containing compound in the carbon source is heptanoic acid (the number of oxygen atoms accounts for 8.7%).

[0074] Comparative Example 15 The difference between this comparative example and Example 8 is that sodium chloride is replaced by potassium chloride.

[0075] Comparative Example 16 The difference between this comparative example and Example 8 is that the oxygen-containing compound in the carbon source does not contain sorbitol.

[0076] Comparative Example 17 The difference between this comparative example and Example 8 is that the oxygen-containing compound in the carbon source does not contain poly(ethylene glycol) tetrahydrofurfuryl ethyl ether.

[0077] Comparative Example 18 The difference between this comparative example and Example 8 is that the step (2) of carbon coating treatment is carbonized at 600°C at one time. In this case, step (2) is as follows: spraying a solution formed by a mixture of saturated sodium chloride aqueous solution and sorbitol onto the surface of the first carbon-coated boron nitride obtained in step (1), and then evaporating at 75°C for 2 h, and then continuing to spray polyethylene glycol 1000 and poly(ethylene glycol) tetrahydrofurfuryl ether, drying after spraying, and vacuum carbonizing at 600°C (heating rate of 10°C / min) for 3.5 h, and then cooling naturally, repeatedly rinsing with clean water to remove sodium chloride, and drying to obtain the second carbon-coated boron nitride.

[0078] Comparative Example 19 The difference between this comparative example and Example 8 is that the carbon coating treatment step (2) is carbonized at 900°C at one time. In this case, step (2) is as follows: spraying a solution formed by a mixture of a saturated sodium chloride aqueous solution and sorbitol onto the surface of the first carbon-coated boron nitride obtained in step (1), and then evaporating at 75°C for 2 h, and then continuing to spray polyethylene glycol 1000 and poly(ethylene glycol) tetrahydrofurfuryl ether, drying after spraying, heating to 900°C (heating rate of 20°C / min) and keeping the temperature for 40 min, then cooling naturally, repeatedly washing with clean water to remove sodium chloride, and drying to obtain the second carbon-coated boron nitride.

[0079] Comparative Example 20 The difference between this comparative example and Example 8 is that the amount of sodium chloride added is 0.5% of the mass of the oxygen-containing compound.

[0080] Comparative Example 21 The difference between this comparative example and Example 8 is that the amount of sodium chloride added is 8% of the mass of the oxygen-containing compound.

[0081] Comparative Example 22 The difference between this comparative example and Example 8 is that the change process of the vacuum degree in the vacuum reaction furnace during the solid phase reaction is as follows: Before heating to 1800℃ and during the 0-1h of heat preservation, the vacuum degree is 4×10 -4 Pa; During the first 2 hours of heating to 1800℃, the vacuum degree was 0.5×10 -4 Pa; The temperature was raised to 1800℃ and kept for 2-3 hours, and the vacuum degree was 3×10 -4 Pa.

[0082] Comparative Example 23 The difference between this comparative example and Example 8 is that the change process of the vacuum degree in the vacuum reaction furnace during the solid phase reaction is as follows: Before heating to 1800℃, the vacuum degree was 8×10 -4 Pa; The temperature was raised to 1800℃ and kept for 0-2h, and the vacuum degree was 0.5×10 -4 Pa; The temperature was raised to 1800℃ and kept for 2-3 hours, and the vacuum degree was 3×10 -4 Pa.

[0083] Comparative Example 24 The difference between this comparative example and Example 8 is that the change process of the vacuum degree in the vacuum reaction furnace during the solid phase reaction is as follows: Before heating to 1800℃, the vacuum degree was 8×10 -4 Pa; The temperature was raised to 1800℃ and kept for 0-2h, and the vacuum degree was 4×10 -4 Pa; The temperature was raised to 1800℃ and kept for 2-3 hours, and the vacuum degree was 3×10 -4 Pa.

[0084] Comparative Example 25 The difference between this comparative example and Example 8 is that the change process of the vacuum degree in the vacuum reaction furnace during the solid phase reaction is as follows: Before heating to 1800℃, the vacuum degree was 8×10 -4 Pa; The temperature was raised to 1800℃ and kept for 0-1h, and the vacuum degree was 4×10 -4 Pa; The temperature was raised to 1800℃ and kept for 1-3 hours, and the vacuum degree was 0.5×10 -4 Pa.

[0085] 1. Particle size of boron carbide nanopowder prepared by the present invention The boron carbide nanopowder product obtained in Example 8 of the present invention was scanned by electron microscope, and the results are shown in FIG. Figure 1 It can be seen that the powder particle size distribution is uniform and the appearance is good. The XRD spectrum of the product powder is shown in Figure 2 , it can be seen that the product is boron carbide powder.

[0086] The particle sizes of the boron carbide nanopowders obtained in Examples 1-10 of the present invention are respectively measured and are shown in Table 1.

[0087] Table 1

[0088] It can be seen from Table 1 that the boron carbide nanopowders prepared in Examples 1-10 of the present invention are in the range of 30-150 nm. By comparing Examples 1-6, it can be seen that the particle size of the powder prepared in Example 6 is smaller. Examples 8-10 use hexagonal boron nitride of different particle sizes as raw materials, and the boron carbide nanopowder prepared in Example 9 (using 50 nm hexagonal boron nitride as raw material) has a smaller particle size.

[0089] 2. Effect of Carbon-Coated Hexagonal Boron Nitride of the Present Invention 1. Dispersion and coating strength of boron nitride powder after carbon coating The dispersion and coating strength of 50 nm, 100 nm, and 200 nm hexagonal boron nitride powders, as well as the carbon-coated boron nitride powders obtained in Examples 1-10 and Comparative Examples 3-14 were observed respectively. The results are shown in Table 2.

[0090] The test method for coating strength is: Weigh a certain amount of the powder to be tested, add it into anhydrous ethanol, start the mixer and stir it at a speed of 1500 rpm for 15 minutes. Use an optical microscope to observe the breakage of the powder surface during stirring in anhydrous ethanol to test the coating strength of the carbon-coated boron nitride powder.

[0091] Table 2

[0092] It can be seen from Table 2 that, compared with the hexagonal boron nitride raw materials (50 nm, 200 nm), the carbon coating treatment of the nano-scale hexagonal boron nitride in Examples 1-10 of the present invention can significantly improve the powder dispersion without agglomeration.

[0093] Compared with comparative examples 3-11, the first carbon coating of Examples 1-10 of the present invention uses a specific ratio of hexose and pentose as the hydrothermal carbonization material, and the second carbon coating uses an oxygen-containing compound with a specific oxygen atom ratio as the high-temperature carbonization material. The combination of the two can obtain better modified powder dispersibility and coating strength.

[0094] 2. Carbonization rate of boron nitride powder after carbon coating The carbonization rates of hexagonal boron nitride subjected to carbon coating treatment in Examples 1-8 of the present invention and Comparative Examples 15-21 were measured respectively. The results are shown in Table 3.

[0095] Table 3

[0096] The higher the carbonization rate of the carbon coating treatment, the better the carbonization effect, and the more complete the reaction between carbon and boron nitride. As shown in Table 3, the carbonization rates of hexagonal boron nitride subjected to carbon coating treatment in Examples 1-8 of the present invention are in the range of 30.57%-46.85%, among which the carbonization rates of Examples 7 and 8 are higher.

[0097] Compared with Example 8, Comparative Example 15 changed sodium chloride to potassium chloride, Comparative Examples 16-17 changed the composition of oxygen-containing compounds, Comparative Examples 18 and 19 changed the carbonization temperature of different steps, and Comparative Examples 20 and 21 changed the amount of sodium chloride added. As a result, the carbonization rate decreased.

[0098] 3. Basic properties of the boron carbide nanopowder prepared by the present invention 1. Yield and purity of boron carbide nanopowder The yield and purity of the boron carbide nanopowders obtained in Examples 1-10 of the present invention and Comparative Examples 1-8 and 15-21 were measured. The results are shown in Table 4.

[0099] Table 4

[0100] As can be seen from Table 4, the yields of the boron carbide nanopowders prepared in Examples 1-10 of the present invention are in the range of 90.0%-98.5%, and the purities are in the range of 91.0-99.5%, among which the yields and purities of Examples 8-10 are higher.

[0101] By comparing Examples 1-6, it can be seen that when the carbohydrate compounds in Example 6 are glucose and xylose, and the oxygen-containing compounds are sorbitol, polyethylene glycol, and poly(ethylene glycol) tetrahydrofurfuryl ether, the yield and purity of the boron carbide nanopowder are higher.

[0102] Based on Example 6, in Example 7, sodium chloride is added during the carbon coating process to improve the solid phase reaction effect. Based on Example 7, in Example 8, the vacuum degree in the solid phase reaction is designed, and as a result, the reaction yield and purity are further improved.

[0103] Compared with Example 6, Examples 1-8 changed the specific steps of carbon coating. Compared with Example 8, Example 15 changed sodium chloride to potassium chloride. Examples 16-17 changed the composition of oxygen-containing compounds. Examples 18 and 19 changed the carbonization temperature of different steps. Examples 20 and 21 changed the amount of sodium chloride added. As a result, the yield and purity of Examples 1-8 and 15-21 decreased to varying degrees.

[0104] 2. Oxygen content of boron carbide nanopowder The oxygen content of the boron carbide nanopowders prepared in Examples 6-10 and Comparative Examples 15 and 18-21 was analyzed. The results are shown in Table 5.

[0105] Table 5

[0106] The higher the oxygen content of the boron carbide nanopowder, the more likely it is to affect the performance of the boron carbide product. As shown in Table 5, the oxygen content of the boron carbide nanopowders prepared in Examples 6-10 of the present invention is in the range of 0.05-0.47%, among which the oxygen content of Examples 8-10 is relatively low, between 0.05-0.08%, which is conducive to improving the sintering performance of boron carbide.

[0107] 3. Fluidity of boron carbide nanopowder The fluidity index of the boron carbide nanopowders obtained in Examples 6-10 of the present invention and Comparative Examples 22-25, i.e., the angle of repose, was measured. The results are shown in Table 6.

[0108] Table 6

[0109] It can be seen from Table 6 that, compared with Examples 6 and 7, in Examples 8-10 of the present invention, the vacuum degree change process is controlled during the solid phase reaction to prepare boron carbide nanopowders, and the repose angle of the obtained powders is controlled below 40°, and the powder fluidity is significantly improved.

[0110] Compared with Example 8, Comparative Examples 22-25 respectively changed the vacuum degree variation process in the solid phase reaction, resulting in poor powder fluidity.

[0111] 4. Sintering properties of boron carbide nanopowders prepared by the present invention The boron carbide nanopowder was sintered by the method of Examples 6-10 of the present invention and Comparative Examples 15, 18-25, and the sintering properties thereof were measured. The results are shown in Table 7.

[0112] Table 7

[0113] As shown in Table 7, the boron carbide nanopowders prepared in Examples 6-10 of the present invention have good sintering properties, with relative density ranging from 98.2% to 99.6%, hardness ranging from 29.5% to 33.5 GPa, and fracture toughness ranging from 2.81% to 5.85 MPa·m 1 / 2 In particular, in Examples 8-10, the vacuum degree variation process is controlled during the solid phase reaction to prepare the boron carbide nanopowder, and the sintering performance of the obtained boron carbide nanopowder is better.

[0114] Compared with Example 8, Comparative Examples 15 and 18-21 changed the carbon coating treatment steps of hexagonal boron nitride, and Comparative Examples 22-25 changed the vacuum degree change process in the solid phase reaction. As a result, the sintering properties of the boron carbide nanopowders were all deteriorated.

Claims

1. A method for preparing boron carbide nanopowder, characterized in that: The following steps are involved: After the hexagonal boron nitride is subjected to carbon coating treatment using a carbon source, the hexagonal boron nitride is placed in a vacuum reactor for solid phase reaction, wherein the carbon source includes a sugar compound and an oxygen-containing compound; The carbon coating process comprises the following steps: (1) The sugar compound and hexagonal boron nitride are mixed and ball-milled, the obtained mixed powder is evenly dispersed by adding water, and then hydrothermal carbonization is performed to obtain the first carbon-coated boron nitride; (2) Spraying an oxygen-containing compound onto the surface of the first carbon-coated boron nitride obtained in step (1), cooling and drying, and then placing it in a sealed state for carbonization at 500-1000° C. for 3-6 hours, and cooling naturally to obtain a second carbon-coated boron nitride.

2. The preparation method according to claim 1, characterized in that: The molar ratio of the carbon source, calculated as C, to hexagonal boron nitride is (1.1-1.6):4, and the diameter of the hexagonal boron nitride is 0.001-50 μm.

3. The preparation method according to claim 1, characterized in that: The mass ratio of the carbohydrate compound to the oxygen-containing compound is (0.5-2):1, and the carbohydrate compound includes hexose and pentose in a mass ratio of 1:(0.3-0.6), the hexose is one or more of glucose, mannose, fructose and galactose, and the pentose is one or two of xylose and deoxyribose; the number of oxygen atoms in the oxygen-containing compound accounts for 10-24%, and the oxygen-containing compound is one or more of polyethylene glycol, poly(ethylene glycol) tetrahydrofurfuryl ether, mannitol, and sorbitol.

4. The preparation method according to claim 1, characterized in that: The temperature of the solid phase reaction in the vacuum reactor is 1500-2000℃, the heating rate is 30-50℃, the insulation time is 3-6h, and the vacuum degree in the vacuum reactor is (0.1-10)×10 -4 Pa.

5. The preparation method according to claim 1, characterized in that: In step (1), the ball milling rate is 300-500 rpm, and the ball milling time is 3-8 h; the hydrothermal carbonization conditions are: 160-250°C, a heating rate of 1-10°C / min, and a heat preservation time of 2-4 h; In step (2), the carbonization heating rate is 5-30°C / min.

6. The preparation method according to claim 3, characterized in that: The oxygen-containing compound comprises sorbitol, polyethylene glycol and poly(ethylene glycol) tetrahydrofurfuryl ether, and the mass ratio of the three is (0.001-0.004):(0.2-0.8):1; The carbon coating process comprises the following steps: (1) The sugar compound and hexagonal boron nitride are mixed and ball-milled, the obtained mixed powder is evenly dispersed by adding water, and then hydrothermal carbonization is performed to obtain the first carbon-coated boron nitride; (2) Spraying a solution formed by a mixture of a saturated sodium chloride aqueous solution and sorbitol onto the surface of the first carbon-coated boron nitride obtained in step (1), and then placing it at 70-80°C for constant temperature evaporation for 1-3 hours, and then continuing to spray polyethylene glycol and poly (ethylene glycol) tetrahydrofurfuryl ether, drying after spraying, first placing it at 500-750°C for vacuum carbonization for 2-5 hours, and then heating it to 850-1000°C and keeping it warm for 0.5-1 hour, and then cooling it naturally, repeatedly washing it with clean water to remove sodium chloride, and drying it to obtain a second carbon-coated boron nitride.

7. The preparation method according to claim 6, characterized in that: The amount of sodium chloride added is 1-6% of the mass of the oxygen-containing compound, the rate of heating to 500-750°C is 5-20°C / min, and the rate of heating to 850-1000°C is 15-30°C / min.

8. The preparation method according to any one of claims 1 to 7, characterized in that: The change process of vacuum degree in the vacuum reactor during solid phase reaction is as follows: Before heating to 1500-2000℃, the vacuum degree is (6-10)×10 -4 Pa; During the 0-1h period of heating to 1500-2000℃, the vacuum degree is (3-5)×10 -4 Pa; During the first 2 hours of heating to 1500-2000℃, the vacuum degree is (0.1-1)×10 -4 Pa; During the 2-6h period of heating to 1500-2000℃, the vacuum degree is (2-4)×10 -4 Pa.

9. A method for sintering boron carbide nanopowder, characterized in that: The following steps are involved: The boron carbide nanopowder prepared in claim 1 is sintered for 40-70 minutes in an inert gas atmosphere at 1900-2100° C. and 28-32 MPa to obtain the boron carbide nanopowder.

10. A boron carbide ceramic, characterized in that: The boron carbide ceramic is made by the sintering method described in claim 9.

Citation Information

Patent Citations

  • Method for preparing carbon coated hexagonal boron nitride

    CN102502535A

  • Method for preparing carbon coated boron carbide (B4C) nano powder

    CN108249443A

  • High-dispersion amorphous carbon coated hexagonal boron nitride nanosheet and preparation method thereof

    CN112662449A

  • Method for preparing high-purity boron carbide powder

    CN101712473A

  • Preparation method for pressureless-sintered boron carbide ceramics

    CN107417280A

Cited By

  • H-BN-coated WC core-shell structure composite material and preparation method and application thereof

    CN121849958A